Retirees’ skills and involvement in society for national development - Yahya, Khulida Kirana; Johari, Johanim; Adnan, Zurina; Mohd Isa, Mohd Faizal; Daud, Zulkiflee (Universiti Teknologi Malaysia, 2008)
Malaysia has been forecasted as an ageing society by the year 2020 due to the expected rise of the number of senior citizens to 2.71 million. This portion includes the government retirees who have reached their mandatory retirement age of 56 years old. The objectives of this study are to analyze the retirees’ profiles and skills and to examine their involvement in associations. To elicit data, a total of 1609 questionnaires were gathered and analyzed using SPSS. Findings indicate that most of the retirees have acquired various skills throughout their years of service, especially in the area related to their tasks and responsibilities. However, these retirees were unable to utilize their invaluable skills appropriately. It is therefore of high importance for the government and non-government bodies to develop a proper means for the retirees to utilise their skills. Recommendations bring to fore several measures that can be undertaken by the relevant authorities to help government retirees optimize their skills in the society for the national development.